1997
DOI: 10.1046/j.1365-2133.1997.18141912.x
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole pulse therapy is effective in the treatment of tinea capitis in children: an open multicentre study

Abstract: In an open multicentre study we have demonstrated that itraconazole pulse therapy, 5 mg/kg per day, is effective and safe in the management of tinea capitis in 10 children (seven boys, three girls, mean age: 6.6 years, age range 4-11 years). The causative organisms were Trichophyton tonsurans (six cases), T. violaceum (two cases), T. soudanense (one case) and Microsporum gypseum (one case). Each pulse of drug therapy lasted 1 week with 2 weeks off between consecutive pulses. One, two and three pulses produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 16 publications
1
46
0
1
Order By: Relevance
“…However, all 9 non-responders had this dermatophyte, suggesti ng that the durati on of therapy has to be extended beyond 2 weeks in certain cases of T. rubrum infecti on. Although the number of cases resulti ng from other pathogens was small, they do respond to this short-term therapy with drug usually in Tenia capiti s. [6][7][8][9][10][11][12][13] Bothitraconazole and terbinafi ne are highly lipophilic and kerati nophilic. They persist in the stratum corneum and hair in high concentrati ons for 3-4 weeks aft er therapy is disconti nued.…”
Section: Discussionmentioning
confidence: 99%
“…However, all 9 non-responders had this dermatophyte, suggesti ng that the durati on of therapy has to be extended beyond 2 weeks in certain cases of T. rubrum infecti on. Although the number of cases resulti ng from other pathogens was small, they do respond to this short-term therapy with drug usually in Tenia capiti s. [6][7][8][9][10][11][12][13] Bothitraconazole and terbinafi ne are highly lipophilic and kerati nophilic. They persist in the stratum corneum and hair in high concentrati ons for 3-4 weeks aft er therapy is disconti nued.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of itraconazole treatments, only one study has shown that, for most dermatophytes, the sensitivity in vitro could be correlated to those in vivo [21]. In a retrospective study, T. violaceum (2 cases), T. soudanense (1 case), T. tonsurans (6 cases) and M. gypseum (1 case) in tinea capitis were shown to respond to itraconazole pulse therapy [8]. …”
Section: Discussionmentioning
confidence: 99%
“…A double-blind comparative study with griseofulvin revealed that the two drugs had similar efficacy but there was a better tolerance for itraconazole [5]. Other studies have confirmed the high efficacy and tolerability of itraconazole in tinea capitis [6, 7, 8]. Terbinafine belongs to the allylamine class of antifungals that also inhibit the synthesis of ergosterol but at a different stage in the synthesis pathway as the azole compounds; it inhibits the squalene epoxidase, an enzyme that catalyzes the conversion of squalene to squalene 2,3-epoxide.…”
Section: Introductionmentioning
confidence: 98%
“…With M. canis tinea capitis a duration of 4 -6 weeks may be required. The number of pulses required for treatment is in part dependent upon the severity of the tinea capitis [259,262,263]. The number of pulses required for treatment is in part dependent upon the severity of the tinea capitis [259,262,263].…”
Section: Ef Cacymentioning
confidence: 99%